PENERAPAN KEGIATAN LINGKUNGAN HIDUP DI PONDOK PESANTREN (Pesantren Islamic Center Bin Baz Piyungan, Pesantren Krapyak & Pesantren Muâallimin Yogyakarta) - , SLAMET ABADI, Dr. M. Baiquni, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Human behavior can be influenced by the level of knowledge, education and family income. The purpose of this study were 1) Getting an overview of the current situation surrounding the Islamic Center Bin Baz boarding school of Piyungan, Krapyak boarding school and Mu'allimin boarding school Yogyakarta. 2) Knowing the studentsâ knowledge about the environment at the boarding school. 3) Knowing the appreciative, creative, proactive, and productive behavior in the students. 4) Knowing the influence of studentsâ environmental knowledge toward the studentâs behavior. 5) Knowing the influences studentsâ education level toward studentâs behaviors. 6) Knowing the influence of family income level toward studentâs behavior. The research used a survey method with (1) a descriptive analysis, (2) a simple regression analysis and multiple regressions. The population is all students who live in the boarding school by random probability sampling technique with total 105 respondents from three schools of each 35 students, by proposing hypotheses, 1) The higher studentsâ knowledge about the environment is followed by higher appreciative attitude, creative, proactive and productive of students. 2) The higher studentsâ education level is followed by higher appreciative, creative, proactive and productive studentâs behavior. 3) The higher family income is followed by appreciative, creative, proactive and productive studentâs behavior. The results of this study were 1) policies of environmental management in three boarding schools that had the highest percentage 82.00% were PP Mu'allimin, then PP Bin Baz Islamic Center 74.00%, and PP Krapyak 56, 00%, but there were lack of environment curriculum. 2) Mean of studentsâ environment Knowledge from the highest percentage was PP Mu'allimin 75.79%, PP Krapyak 75.64% and PP ICBB 75.59%. 3) Average value of Appreciative, Creative, Proactive, and Productive Behaviors in the boarding schools from the highest percentage was PP ICBB 73.46%, Krapyak PP 70.11% and PP Mu'allimin 65.61%. 4) There was a significant effect between students knowledge about environment (X1) toward students behavior (Y) with a 0.00 significance value <0.05. 5) There was no significant effect between studentsâ education level on the students behavior by significance value 0.376> 0.05. 6) There was no significant effect of family income on studentâs behavior by significance value 0.333> 0.05.